Sistem irigasi Regentschap Nganjoek tahun 1900-1934 - Retha Herdian Putri; Ronal Ridhoi (Historiography: Journal of Indonesian History and Education, 2023)
Regentschap Nganjoek is an area that has experienced drought problems during the dry season and floods during high rainfall since the 20th century. This study attempts to describe the condition of Regentschap Nganjoek prior to the repair or development of irrigation and the irrigation development process in the region. The areas where irrigation is built are located along the Brantas River which has an important role for the community such as agriculture and the plantation industry. The Brantas River has also had an impact on flooding and drought in Nganjuk, so it is necessary to repair and develop irrigation in the form of canals and drainage. This study applies the historical method by utilizing various sources such as written archives such as colonial records, newspapers, and magazines. In addition, photos of irrigation development and other sources were found. This article shows that the repair and development of irrigation in Regentschap Nganjoek aims to maintain water availability and be able to overcome flooding in the early 20th century.Regentschap Nganjoek merupakan daerah yang memiliki masalah kekeringan pada musim kemarau dan banjir pada saat curah hujan yang tinggi sejak abad ke-20. Kajian ini mencoba menggambarkan kondisi bagaimana Regentschap Nganjoek sebelum adanya perbaikan atau pembangunan irigasi dan proses pembangunan irigasi di wilayah tersebut. Daerah yang dijadikan tempat pembangunan irigasi berada di sepanjang aliran Sungai Brantas yang memiliki peran penting untuk masyarakat seperti pertanian dan industri perkebunan. Sungai Brantas juga menimbulkan dampak banjir dan kekeringan di Nganjuk sehingga diperlukan perbaikan dan pembangunan irigasi berupa kanal dan drainase. Penelitian ini menerapkan metode sejarah dengan memanfaatkan berbagai sumber seperti arsip tertulis seperti catatan kolonial, surat kabar, maupun majalah selain itu ditemukan foto pembangunan irigasi dan sumber lainnya. Artikel ini menunjukkan bahwa adanya perbaikan dan pembangunan irigasi di Regentschap Nganjoek bertujuan untuk menjaga ketersedian air dan dapat menanggulangi banjir di awal abad ke-20.